Design, Synthesis, Anticancer Activities and Comparative Molecular Docking Studies of a Novel Class of 7-Azaindole Analogs as Potent PARP-1 Inhibitors - Sharma, Neha; Chaudhary, Anurag; Sachdeva, Monika (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: In a research facility, 7-azaindole derivatives were designed and synthesized, and each substance was examined for its capacity to inhibit cancer growth. In the present study, the synthesized analogues were docked with PARP enzyme to find a suitable site for PARP inhibition. Materials and Methods: 1H nuclear magnetic resonance, 13C NMR, and mass spectrometry were used to characterize all synthesized analogues of 7-azindole. On the MCF-7 cell line for breast cancer, their anticancer activity was assessed. The proteins of PARP-1 inhibitors were docked against using the protein IDs 6NRF, 6NRG, 6NRH, 6NRI, 6NRJ, and 6NTU. For 7-azaindole derivatives, the two docked proteins 6NRH and 6NRF performed best. Results: The most active compound against MCF-7 cell lines has a GI50 of 15.56 μM, which is compound 4g. The compounds 4a, 4b, 4c, 4i, and 4h also exhibited good anticancer activity so these compounds have the prospective to be used as PARP inhibitors. According to additional molecular docking studies these compounds can bind to protein targets 6NRH well. These compounds offer promising potential as PARP inhibitors for the development of novel medications. Conclusion: The results of the study were favorable and gave direction for the synthesis of some novel potent 7-Azaindole compounds as a PARP inhibitors.
Keywords: 7-azaindole; Synthesis; Docking; Anticancer activity; PARP inhibitor